2001
DOI: 10.1111/1468-0092.00140
|View full text |Cite
|
Sign up to set email alerts
|

The Earliest Evidence for Metal Bridle Parts

Abstract: Recent discoveries in different parts of the Near East have led the authors to reconsider the early history of metal driving bits. These now seem to go back into the third millennium BC, which is much earlier that the evidence previously indicated. The paper also includes a brief discussion of the links -if these existed at all -with early bridle bits made of organic materials from the southern Urals-Volga area.The recent discovery at Tel Haror in the northern Negev of a copper/bronze bridle bit on an equid bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…BCE) at Tell Brak in northern Mesopotamia (modern Syria), it has been suggested that the differential wear visible on anterior face of the LPM2 of donkey teeth was a function of bit wear [ 11 , 14 , 15 , 61 ]. In addition, there is a ceramic plaque recovered from Akkadian deposits at Kish that depict an ass or onager being ridden [ 17 , 19 , 62 ].…”
Section: Antiquity Of the Bit In The Near Eastmentioning
confidence: 99%
“…BCE) at Tell Brak in northern Mesopotamia (modern Syria), it has been suggested that the differential wear visible on anterior face of the LPM2 of donkey teeth was a function of bit wear [ 11 , 14 , 15 , 61 ]. In addition, there is a ceramic plaque recovered from Akkadian deposits at Kish that depict an ass or onager being ridden [ 17 , 19 , 62 ].…”
Section: Antiquity Of the Bit In The Near Eastmentioning
confidence: 99%
“…The copper bridle bit was made of a solid-forged, round-sectioned (1.1 cm) bar mouthpiece and a pair of cast discoid cheek pieces that are studded on their inner face (Figure 4 and Figure S5; [16], [20]; Specimen IAA # 2009-951, The Israel Museum, Jerusalem). The 6.3 cm diameter cheek-pieces are ‘spoke-wheeled’ and include loops for the attachment of the cheek straps of the headstall and to the central hole for the mouthpiece bar.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the Haror example, most known finds of typologically similar metal bits are of uncertain date or of unknown provenance ([20]:333 [22], [25]). At the site of Tell el-Ajjul in nearby Gaza, and not far from Haror, Petrie [26] discovered a typologically similar bridle bit but unfortunately its context is not clearly defined [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations